TRANSLATION PROBLEMS OF EDUCATIONAL TERMS (Journal of Universal Science Research, 2023)
The paper presents an analysis and translation of some terms of education in linguistics. The sphere of research work has become the terminology of the communicative methodology of teaching English. When translating terms, the main task is to create an adequate translation.